Serum level of IL-8 is associated with reversion of QuantiFERON-TB gold in-tube tests. Issue 4 (April 2019) - Xin, Henan; Zhang, Haoran; Cao, Xuefang; Li, Xiangwei; Li, Mufei; Feng, Boxuan; Jin, Qi; Gao, Lei
Highlights: Frequent QFT reversion observed in serial tests has not been fully understood. Serum level of IL-8 were significantly associated with QFT reversion. IL-8 may be used as biomarker to support reversion caused by infection clearance. Summary: Background: Frequent reversion has been commonly observed in serial QuantiFERON-TB Gold In-Tube (QFT) tests, which limited its accuracy in defining the status of Mycobacterium tuberculosis (MTB) infection. Serum cytokine profiles might provide additional information to clarify the infection status. Method: Based on a population-based cohort study aiming to track MTB infection acquisition and disease development, serum profiles of 12 cytokines were determined by bead-based multiplex assays in parallel with QFT and tuberculin skin tests (TST) to explore potential relation between serum cytokines and MTB infection status. Results: Totally, 309 subjects got QFT conversion in one year (2013–2014) and 46.92% (145/309) of them got reversion in 2015. The study subjects were classified into three groups according to their QFT and TST results in 2015 (QFT persistence positive, QFT-/TST + and QFT-/TST-). The serum levels of MCP-1 and IL-8 were significantly different among the three groups. Furthermore, level of IL-8 was dramatically lower in QFT-/TST- group as compared to the other two groups, and no significant difference was observed for QFT-/TST + group as comparing with persistent positive group. Conclusion: Our results suggested that the decreased serum level of IL-8 might be potential biomarker to identify QFT reversion caused by infection clearance.